Liquid phase oxidation of p-cresol over cobalt saponite - Kshirsagar, Vikas S.; Garade, Ajit C.; Patil, Kashinath R.; Shirai, Masayuki; Rode, Chandrashekhar V. (Topics in Catalysis, 2009)
Liquid phase oxidation of p-cresol was carried out over a Co-saponite catalyst in a temperature and pressure range of 333-393 K and 20-827 kPa, respectively in n-propanol. Co-saponites with varying cobalt content (5-30%) were prepared and screened among which 13% Co-saponite gave the highest conversion of 92% of p-cresol with 92% selectivity to p-hydroxybenzaldehyde without formation of any non-oxidation products.
Keywords: Co-saponite; Liquid phase oxidation; p-Cresol; p-Hydroxybenzaldehyde; XPS

Liquid phase oxidation of p-vanillyl alcohol over synthetic Co-saponite catalyst - Garade, Ajit C.; Biradar, Narayan S.; Joshi, S. M.; Kshirsagar, V. S.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V. (Applied Clay Science, 2011)
Effect of cobalt loading on porosity of synthetic Co-saponite catalysts and on the air oxidation of p-vanillyl alcohol was studied by varying Co content in the range of 5% to 30% using in situ precipitation method. The pore size increased from 1.29 to 3.69 nm indicating a transition from micro to meso porosity, with increase in Co loading from 5% to 30%. The distribution ratio of Co(3)O(4)/CoO phases as estimated from TPR studies, also increased from 0.84 to 1.67 with increase in Co loading from 5% to 13% and remained almost constant (1.7) with further increase in Co loading up to 30%. The highest activity (conversion 55%) and selectivity of 99% to p-vanillin obtained for 13% Co-saponite in p-vanillyl alcohol oxidation was due to the highest distribution ratios of Co(3)O(4)/CoO phases. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Co-saponite; Cobalt oxide phase ratio; p-Vanillin; p-Vanillyl alcohol oxidation; Porosity transition; Temperature programmed reduction